2006
DOI: 10.5650/jos.55.615
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanocapsules with Alginate/Polylysine Complex Wall

Abstract: This paper deals with a novel preparation method of nanocapsules with alginate/polylysine complex wall. The preparation method consisted of the following steps: dispersion of an aqueous sodium alginate solution into cyclohexane to give a W/O emulsion, preparation of calcium alginate gel beads by adding the emulsion into a calcium aerosol OT solution in cyclohexane, and alginate/polylysine complex wall formation on the surface of calcium alginate beads by adding the beads into an aqueous poly-L-lysine solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…W/O emulsions were prepared with the laboratory-made apparatus for electrocapillary emulsification [7,8]. Briefly, the apparatus consists of the emulsification part, the applied electric potential and liquid dropping rate controlling part, a CCD camera and a monitor.…”
Section: Preparation Of Polyurea Capsulesmentioning
confidence: 99%
“…W/O emulsions were prepared with the laboratory-made apparatus for electrocapillary emulsification [7,8]. Briefly, the apparatus consists of the emulsification part, the applied electric potential and liquid dropping rate controlling part, a CCD camera and a monitor.…”
Section: Preparation Of Polyurea Capsulesmentioning
confidence: 99%
“…The electrostatic atomization is a technique for the atomization of liquid with an electrohydrodynamic (EHD) force, and many studies are reported in recent years . The electrostatic atomization could be classified into three systems as follows: (1) a liquid dispersion into a gas (L/G) system, (2) gas dispersion into a liquid (G/L) system, and (3) a liquid dispersion into a liquid (L/L) system.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, although electrostatic emulsification has potential ability to prepare a uniform nano‐size droplet, reports on the production of drug carrier are few. Some attempts for the drug carrier production were conducted by Abe et al , such as the nano‐capsule of alginate/polylysine complex, which has sizes ranging from 100–500 nm, the Poly(2‐ethylcyanoacrylate), which has sizes ranging from 100–300 nm, and the poly‐urea capsule of around 200 nm …”
Section: Introductionmentioning
confidence: 99%
“…Much smaller gel particles are expected to be obtained if they are prepared at the water/oil interface via emulsion droplet. We have recently reported a new preparation method of calcium alginate gel particles in which an aqueous polyelectrolyte solution was dispersed in an oil phase containing oil-soluble gelling agent obtained by modifying a surfactant with calcium ion and gelation occurred on the surface of each aqueous droplet 9 .…”
mentioning
confidence: 99%